Syntax Aspects In Children Development Of Sentence Structure - Siti Ismahani; Budiman Budiman; Khairul Azmi; Hazri Fikri; Gilang Hizbullah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This qualitative study examines the acquisition and understanding of syntax in English as a Foreign Language (EFL) at the undergraduate level. The research explores students' perceptions of syntax, classroom instruction methods, challenges encountered, and the role of context and practice in developing syntax understanding. Data collection methods include classroom observations and semi-structured interviews with undergraduate students enrolled in EFL programs. Thematic analysis is used to identify patterns and themes in the data, providing insights into the complexities of syntax acquisition in EFL contexts. The findings reveal diverse perceptions of syntax among students, highlighting the need for tailored instructional approaches. Classroom observations demonstrate the use of various teaching methods and materials, emphasizing the importance of a balanced approach to syntax instruction. Students report challenges in acquiring syntax, such as understanding complex structures and applying grammar rules accurately, underscoring the need for targeted interventions and support. The study also emphasizes the role of context and practice in developing syntax understanding, with students valuing real-life examples and interactive activities. Based on the findings, the study suggests several implications for EFL instruction, including the need for diverse instructional strategies, an integrated skills approach, the use of authentic materials and contexts, and individualized support. Future research directions are proposed, including longitudinal studies, comparative analyses, investigations into the effectiveness of instructional strategies, and the exploration of technology-enhanced learning. By addressing these research gaps, scholars can contribute to the development of evidence-based practices that support EFL learners in mastering syntax and achieving proficiency in English.